About educating of discipline there is government service (Journal of actual problems of jurisprudence, 2019)
This article discusses features of teaching the course “Public service” for law students and universities. The study of theoreticalconcepts in the theory of public administration and legal foundations of public service organizations, the history of its development inour country, the dynamics of change, the characteristics of receipt, transmission and termination of public service, the experience of developedforeign countries - all of this article the author believes it is necessary not only for researchers, but also for the general students.